Analisis Penerapan Quickresponse Indonesian Standard Dalam Meningkatkan Akuntabilitas Pengelolaan Dana Punia Pada Pura Jagatnatha, Singaraja - Atmika, I Gusti Agung Gede Wahyu Widhi; Sulindawati, Luh Gede Erni (Universitas Pendidikan Ganesha, 2021)
Quick Response Indonesian Standard (QRIS) is a non-cash payment system that use smartphone for its media in which this system was launched by Bank Indonesia. In 2019 Bank Indonesia gave a permission for BPD Bali to launch QRIS. The usage of QRIS BPD Bali is not only for profit transactions, but also as social funding such as punia funds at temples. The purpose of this study was to prove the implications of QRIS for increasing accountability in the management system of punia funds. This study used descriptive qualitative method. The data were obtained through observation, interviews and documentation, which were then carried out by reducing, presenting data and drawing conclusions. The analyzed components were the effectiveness of QRIS, the opinions of pemedek and temple administrators and the implications for the accountability of punia fund management. The results of the study concluded that QRIS was considered ineffective due to lack of socialization, conventional believer mindset and lack of spiritual values so that it failed to provide a significant increase in the accountability of punia fund management at Jagatnatha Temple Singaraja.